The Role of the Laparoscopy on Circumferential Resection Margin Positivity in Patients With Rectal Cancer. Issue 2 (April 2015) - Dural, Ahmet C.; Keskin, Metin; Balik, Emre; Akici, Murat; Kunduz, Enver; Yamaner, Sumer; Asoglu, Oktar; Gulluoglu, Mine; Bugra, Dursun
<x xml:space="preserve">Abstract</x> Background: The aim of this study was to evaluate the influence of laparoscopic rectal cancer surgery on circumferential resection margin (CRM) involvement. Materials and Methods: The data from 579 consecutive patients who underwent laparoscopic or open resection of rectal cancer from October 2002 to August 2008 were analyzed retrospectively. The primary endpoint was CRM status. The secondary endpoints were morbidity, local recurrence rate, overall survival, and disease-free survival. Results: Laparoscopic resections were performed in 266 patients (46%), and the remainder of the patients underwent open resection. The rates of CRM involvement were similar between the laparoscopic and open groups (5.6% vs. 5.4%). The perioperative morbidity rates between the 2 groups were not significantly different (P=0.2). The incidence of local recurrence for the CRM-negative group was 8.4% (8.3% laparoscopic vs. 8.45% open; P=0.99), whereas the local recurrence rate was 34.3% for the CRM-positive group. The local recurrence rate was 20% for the CRM-positive patients in the laparoscopic group and 47% for the CRM-positive patients in the open group (P<0.001). We did not observe any significant differences in local recurrence rates between the Lap R and Open R groups after omitting CRM status. CRM positivity was correlated with both 5-year survival and the 5-year disease-free survival rate (P=0.009 and P=0.001, respectively). We did not observe any significant differences in morbidity, local recurrence, or overall or disease-free survival rates between the overall laparoscopic and open resection groups. Conclusions: Laparoscopic surgery for rectal cancer is associated with similar complication rates, CRM involvement status, and long-term outcomes as those associated with open surgery but with the advantages of minimally invasive surgery. Although laparoscopic surgery might necessitate more advanced technical skills, similar long-term oncological results can be obtained with this technique.